The Effect of Personality and Learning Motivation on Students’ English Reading Skills - Dela Safitri; Suryadi, Suryadi (ETERNAL (English Teaching Journal), 2024)
The study aims to explore the influence of personality and learning motivation on students' English reading skills. Individual personality can play an important role in the learning process, while learning motivation is a key factor that affects student skill levels. The study involved the participation of students from a variety of backgrounds, using quantitative methods to collect data through questionnaires and experiments using 2x2 design factorials. Students with more open personalities tend to show improvements in their reading skills. Moreover, learning motivation also has a significant impact on reading skills, with students with high motivation tending to have better reading skill levels. The population in this study was class XI of SMAN 1 Bojonegara with samples selected by random sampling which amounted to 68 students. The instruments used were test and questionnaire with the form of 20 multiple choice questions and 30 questionnaire. For data collection techniques in this study using test and questionnaire. The results showed a significant effect between student personality and learning motviation on students reading skill. The F0 value is 5.072 and Sig. is 0.028 < 0.05. Thus, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. That is, there is an interaction between student personality and learning motivation on students reading skill